Study Effect of Dezincification on the Fatigue Properties of Brass Alloy - Hussein, Hussein Jabbar; Al-Kaisy, Hanaa A.; Elie, Saad M. (Al-Khwarizmi Engineering Journal, 2009)
This research includes a study of dezincification by corrosion from brass alloys in three types of media, which are acidic solution, basic and slat solution in different percentages. The study show the higher dezincification occurs in basic solution which decrease the fatigue properties where the fatigue properties are inversely proportional with dezincification.